Arduino-Based Mosquito Trap Design - Achmad Syauqii; Zulfikar Zulifkar (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Mosquitoes are widely recognized as carriers of dangerous diseases such as dengue fever, malaria, chikungunya, and Zika, which pose serious public health problems in tropical regions. Conventional mosquito control methods, including chemical spraying, coils, and fogging, have several disadvantages, such as health risks, environmental pollution, and reduced effectiveness due to mosquito resistance. This study presents the design and implementation of an automatic mosquito trap based on Arduino Uno as a safer and environmentally friendly alternative. The system was developed by integrating temperature and humidity sensors, light sensors, an ultraviolet lamp, and a direct current fan, which were controlled by a microcontroller and relay modules. The operational logic was programmed so that the lamp activated in low light conditions with optimal temperature and humidity for mosquito activity, while the fan provided suction to direct mosquitoes into a container. The device was assembled and tested indoors to evaluate its automatic functionality. Results showed that the system consistently responded to environmental conditions by activating components without human intervention, effectively attracting and trapping mosquitoes. The prototype demonstrated reliable operation, low power consumption, and the potential for practical use in residential areas. This research indicates that an automatic mosquito trap designed with microcontroller technology can provide an effective and chemical-free solution for mosquito control, with the possibility of future development including improved design, alternative energy sources, and wireless monitoring capabilities.